Finding New Regional Mandalas: Indonesia Maritime Strategy Between India And China - Effendi, Yusli (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
This paper aims to analyse Indonesia?s dilemmas and prospects in engaging maritime strategic partner between China and India while pursuing its maritime reorientation. The expanding presence of China in Indian Ocean and its aggressiveness in maritime territorial dispute in East Asia has triggered India to transform Rao?s ?Look East policy? to Modi?s ?Act East policy?.  Modi?s ambitious foreign policy increased eastward focus and his commitment in pursuing economic growth has been combined with India?s strategy in balancing against China?s Silk Road strategy. Both emerging powers, China and India, see Indonesia potential as strategic maritime partner in their strategic vision. Utilizing New Maritime Silk Road strategy or One Belt One Road (OBOR) Initiative in 2013, China engages ASEAN, including Indonesia, in infrastructure construction mega-project to enhance connectivity. While India, began in 1996 as dialogue partner in ASEAN Regional Partner (ARF), gets more involved in as ASEAN partner by joining ASEAN Defence Ministers Meeting Plus (ADMM+) in 2010 and Expanded ASEAN Maritime Forum (EAMF) in 2015. India and Indonesia have shared the common view of culture, colonial history, and political sovereignty, economic self-sufficiency, and independent foreign policy. Theyhave been also originated from the same ancient polity that habituate them to cooperate even under anarchy situation. However, this mandala-inspired cultural legacy would also drive them toward potential conflict as the two countries try to structure their spatial process centripetally using maritime strategy. In this regards, the paper will also discuss the continuity and dissonance of maritime perspective in Indonesia and India experience. Jakarta?s will to strengthen its maritime posture marks its leitmotif to play its role as center within Southeast Asia mandala will be contested by India and China strategic interests in the sea.  In the cultural memory of region, exerting power on the sea and ownership of huge armada symbolically marks and legitimates a country?s supremacy within heterarchy or regional hierarchy that tends to be equal. Using both contemporary and classical literature, this research intends to reveal how the contending emerging powers seek to aspire regional leadership using maritime tradition.  While embarking from leadership-generational change and historical experience, this paper will shed the light why maritime strategy acts as guiding principles for national security in the global geopolitical shift and regional geo-strategy.